A Work study on Network Filter Fabrics Industrial Corporation - De Guzman, Rhedd Jorge; De Leon, Ricci N.; Lim, Tecson John S.; Plagata, Rheanne R. (College of Engineering, 1997)
Network Filter Fabrics Industrial Corporation, a manufacturer of varied lines of filter products and bulk bags, is a small, relatively young, but rapidly progressing company. Its product demand (by job-orders) is steadily growing, resulting to an expansion of labor force, additions to product line respective of specification and sizes, bulk orders of raw materials, appropriations of new equipment and an impending transfer to a bigger plant. These adjustments should, expectedly, result to increased total profit. However, though marginal profit seems to have improved to a considerable increment, NFF's management believes that production yield is not taken to its optimal as supported by recent post-accounting data. A recent peak demand season, in fact, resulted to fierce overtime schedules; but after post-accounting, yield showed almost equal to regular production schedule. This, to the apprehension of management, forced to the adoption of a new system--a quota-based production and labor payment, instead of the usual time-based. Although production now seems to be proceeding smoothly in this new system, management is aware of the possibility that inoptimal production is caused by inherent factors in operations--not just the simple fault of the system. The main suspect, in fact, is the lack of production standards. Therefore, management requested for this Work Study. Therefore, this Work Study's main goal is to standardize future production schedules for planning by stating standard times of its scope and subsequently, propose improvements on working conditions, methods and aspects of production policy. This study follows textbook Work Study methodology to achieve these goals.Due to time constraint and advice of management, only the bulk bag with common specification (90 cm x 90 cm x 120 cm) is focused upon in this study. This bulk bag is the key-profit generating product of NFF. Data regarding the production of the bulk bag and the company operations, in general, are gathered through numerous plant visits and interviews of key personnel. Specifically, the processes-cutting, sewing, trimming inspection and packing-involved in the production of the bulk bag are individually documented with respect to, where applicable, their equipments, workers involved, working methods, duration, system of implementation, and control factors looked upon for quality. Also, the general working condition, plant layout, and company background and general systems and procedures are all properly documented with data. Where needed, technical charts and diagrams of Method Study and Work Measurement are applied for clearer presentations. Then, using the gathered data, production problems of NFF are determined by cause and effect relationships using the appropriate charts, in an attempt to identify and isolate the root problems and recognize its limiting factors. Afterwards, alternatives are formulated and presented with their corresponding pros and cons to solve the problems found. Eventually, only one among the alternatives is chosen and discussed in full, which is the conclusion followed by recommendations. The following are the concrete findings : the quota system is a problem in the long run because of the unreliability of quota determination which, on the first place, is just subjectively done. This is apparent from the current situations of many idle workers who finished their quota early, but are still paid by day. There is clearly no designated storage between work-in-process and finished inventory,if not the storage room providing not enough room. This causes blocked pathways, which delays other operations. There is lack of standard methods. There is lax supervision, quality and working control wise. There should be specific control points and standards to be looked at for quality, and again, the quota system results to lack of control when workers are free to take a break as long as the quota will be finished. There is bottleneck in inspection, showed by the comparison of time between the processes. Some small adjustments should be done regarding housekeeping. Among the alternatives, the one that removes the quota system and proposes a continuous line assembly is the most sound and beneficial to the company. In the first place, the shift to the quota system is more of temporary remedy than a long term solution. The root settlement lies in the establishment of production standards on all aspects, from working assignments per operation to the methods in each operation. The study team recommends adjustments regarding these considerations supported and quantified. A proposed plant layout for the new plant is also presented, which exhibits the most efficient material and process flow for plant operations.